Administrative responsibility for corruption - Бородін, Іван Лук'янович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The corruption problem is still topical and represents the interest for administrative legal science. The author attempted to emphasize the attributes of administrative responsibility for the corruption offences. He based his opinion on the scientific literature, the statutory acts and the Law of Ukraine "On the corruption prevention and counteraction", which was passed on the 7th of April in 2011 and entered into force on the 1st of July in 2011